ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MENABUNG DI LEMBAGA KEUANGAN SYARIAH - Solekah, Nihayatu Aslamatis (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
This paper aims to analyze the factors that considered by customer in making a decision to deposit their money at the Islamic Financial Institutions as well as to analyze the main factors considered by customers in making a decision to deposit in to Islamic Financial Institutions. The research method used is factor analysis. The analysis technique used is through the following stages: Description of Data, Test of variables Interdependence, extraction factor (early statistics), factor before the rotation, Rotation Factor and Validity Test and reliability of the model factor. The samples in this research are 100 respondents from 7 BMT in Malang city. Sampling of customers of Islamic financial institutions in this research is using a purposive sampling technique, which is sampling of customer of Islamic financial institution that intentional without consider the level in the population. This technique is done due to the member of the population is considered homogeneous and already well-known. The results of this study showed that environmental factors that consist of cultural, social class, personal, and family and marketing mix factors that consist of product, place, promotion, and price are the factors that considered by customers when making a decision to deposit their money in to Sharia Financial Institutions. The main factors to be considered are the marketing mix, and environmental factors.